Random candy surprise gifts box / Anjali Sedit - Sedit, Anjali (2022)
In this era, we cannot denied that people straggling do earn more pocket money. Either it’s the elder or even the youngster, everyone started to do their own small business. Hence, business is one of the fun thing to do despite gaining some money for nowadays economy. As for the youngster or fresh graduate, in this era is a bit difficult to get a proper job. A business is the easiest way to gain their own pocket money for continue their living. As for this project, I have proposed a business of gift box which I called^Randpm Candy Surprise Gifts Box. The main reason I chose this business was that I could spend time with my mom by decorating the gifts according to creativity. In addition, 1 was also*able to strengthen the relationship between mother and child. Besides, I also like to see the happy reaction of someone who is happy when receiving a gift from a loved one. Despite that, the type of products I produce is now no stranger in the market or in social media as many sellers first started the business of selling these gift boxes. With the availability of smartphones , people can order gift boxes from me .